Studying Talk to her - Hughes, Emily (Studying films., 2015)
Talk to Her (2002) is a hugely rich and interesting, but ambiguous, film which met with both popular success and critical acclaim. The film won the 2003 Oscar for best original screenplay and has been hailed by some critics as Pedro AlmodOvar's masterpiece. But like most of AlmodOvar's films, little is clear cut; the characters are complex and our affinity and empathy for them shifts throughout the film. In Studying Talk to Her, Emily Hughes provides an in-depth analysis of both the formal elements of the film (narrative, genre, auteur study) and the themes and issues that arise, including the social context of modern Spain and the old traditional iconography, the shifting attitudes towards gender, and, crucially, the uneasy, morally ambiguous depiction of rape and the spectator's reaction to it.